On-Resin Assembly of Macrocyclic Inhibitors of Cryptococcus neoformans May1: A Pathway to Potent Antifungal Agents - Kryštůfek, Robin; Verner, Václav; Šácha, Pavel; Hadzima, Martin; Trajhan, Filip; Starková, Jana; Tloušt'ová, Eva; Dvořáková, Alexandra; Pecina, Adam; Brynda, Jiří; Chalupský, Karel; Hájek, Miroslav; et al. (Journal of medicinal chemistry, 2025)
Macrocyclic inhibitors have emerged as a privileged scaffold in medicinal chemistry, offering enhanced selectivity, stability, and pharmacokinetic profiles compared to their linear counterparts. Here, we describe a novel, on-resin macrocyclization strategy for the synthesis of potent inhibitors targeting the secreted protease Major Aspartyl Peptidase 1 in Cryptococcus neoformans, a pathogen responsible for life-threatening fungal infections. By employing diverse aliphatic linkers and statine-based transition-state mimics, we constructed a focused library of 624 macrocyclic compounds. Screening identified several subnanomolar inhibitors with desirable pharmacokinetic and antifungal properties. Lead compound 25 exhibited a Ki of 180 pM, significant selectivity against host proteases, and potent antifungal activity in culture. The streamlined synthetic approach not only yielded drug-like macrocycles with potential in antifungal therapy but also provided insights into structure-activity relationships that can inform broader applications of macrocyclization in drug discovery.
Keywords: Microbial Sensitivity Tests; Animals; inhibitory proteas; mikrobiální testy citlivosti; antifungální látky; Antifungal Agents; Cryptococcus neoformans; lidé; Structure-Activity Relationship; Protease Inhibitors; vztahy mezi strukturou a aktivitou; makrocyklické sloučeniny; Humans; zvířata; Macrocyclic Compounds